ANALISIS KADAR FITOKIMIA DAN ZAT WARNA DALAM SARI BUAH ANGKUNG HIJAU DAN MERAH (Basella alba and Basella rubra) - Adnan Nur Avif; Ester Dwi Antari (Lantanida Journal, 2022)
The phytochemical compounds and pigments of Basella alba and Basella rubra fruits have been investigated. The extract of mature basella fruits is facile by pressing technique. The extract was analyzed for the total phenolics, flavonoids, anthocyanins, and betalains by spectrophotometer methods. Total phenolic, flavonoid and anthocyanin in Basella rubra extract were Basella alba with values of 62,23 (mg/g GA); 46,78 (mg/g QE) and 0,62 mg/g respectively. Betalain concentration in booth extract was not significantly different at 1,03 mg/g. Antioxidant activity in both fruit juices has an IC50 value of 51,62 mg/mL.